Origin and name of “conglomerate” formation on the top of the Ba Vi moutain - Đông, Bùi Văn; Phương, Tạ Hòa; Dương, Nguyễn Thùy (Vietnam Journal of Earth Sciences, 2014)
There is a bed rock containing a lot of coarses with elliptical and rugby shape on the highest part of the moutain ridges within BaVi range (Vua and Tan Vien ridge). This formation covers igneous rocks of the Vien Nam formation.Currently, there are some opinions about origin of the formation. Some opinions suggest that it was formed by sedimentary process while others suggest that it was formed by volcanic eruption. Results from optical microscopy analysis show that almost samples from both coarses and cements occur as intermediate volcanic rocks including trachyte, dacite and trachydacite. In addition, shape of many coarses shows that they had undergone a plastic deformation process when they were still hot and not cool completely. From these studies, it can be concluded that the coarses are mainly volcanic bombs formed by volcanic eruption. Therefore, this bedrock is an aglomerate formation and it was formed in the eruption forming the Vien Nam formation (P3 vn).